2010
DOI: 10.1084/jem.20090581
|View full text |Cite
|
Sign up to set email alerts
|

TIM1 is an endogenous ligand for LMIR5/CD300b: LMIR5 deficiency ameliorates mouse kidney ischemia/reperfusion injury

Abstract: Leukocyte mono-immunoglobulin (Ig)–like receptor 5 (LMIR5)/CD300b is a DAP12-coupled activating receptor predominantly expressed in myeloid cells. The ligands for LMIR have not been reported. We have identified T cell Ig mucin 1 (TIM1) as a possible ligand for LMIR5 by retrovirus-mediated expression cloning. TIM1 interacted only with LMIR5 among the LMIR family, whereas LMIR5 interacted with TIM4 as well as TIM1. The Ig-like domain of LMIR5 bound to TIM1 in the vicinity of the phosphatidylserine (PS)-binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
118
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 40 publications
5
118
0
Order By: Relevance
“…These findings suggest that the binding of CD300b to TIM1-or TIM4-expressing cells was PS-dependent. TIM1-or TIM4-expressing Ba/F3 cells are known to capture PS-expressing exosomes; 12 thus it is plausible that CD300b does not bind TIM1 or TIM4 directly as previously proposed, 23 but rather associates with these proteins indirectly through associated PS-containing exosomes, or other PS-containing membrane fragments. With this line of reasoning, we hypothesized that the binding affinity of CD300b to TIM1-or TIM4-expressing Ba/F3 cells would increase after the addition of PS-coated liposomes.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…These findings suggest that the binding of CD300b to TIM1-or TIM4-expressing cells was PS-dependent. TIM1-or TIM4-expressing Ba/F3 cells are known to capture PS-expressing exosomes; 12 thus it is plausible that CD300b does not bind TIM1 or TIM4 directly as previously proposed, 23 but rather associates with these proteins indirectly through associated PS-containing exosomes, or other PS-containing membrane fragments. With this line of reasoning, we hypothesized that the binding affinity of CD300b to TIM1-or TIM4-expressing Ba/F3 cells would increase after the addition of PS-coated liposomes.…”
Section: Resultsmentioning
confidence: 85%
“…22 Others have identified the PS-binding receptors TIM1 and TIM4 as endogenous ligands for CD300b, but not PS itself. 23 Here, we show that CD300b binds to PS, and recognizes PS on TIM1 or TIM4 expressing cells rather than TIM1 or TIM4 alone. We found that CD300b promotes PS-dependent apoptotic cell phagocytosis upon ectopic expression in cell lines, without the need for additional PS receptors.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…2 The binding motif WFND has been known to be essential for the phagocytic function of KIM-1. 21 The alignment of zKim-1 with mKIM-1 and hKIM-1 protein sequences demonstrated that the FND residues are conserved, while the tryptophan (W) residue is replaced with leucine (L) ( Figure 3C). The WFND motif is completely conserved in zKim-4.…”
Section: Identification Of Zebrafish Kim-1 Familymentioning
confidence: 99%